Super-hydrophobic MOF-based polyurethane sponge added with green inorganic flame retardant and used for oil-water separation and preparation method of super-hydrophobic MOF-based polyurethane sponge
By loading Ni-MOF and magnesium hydroxide or aluminum hydroxide on the polyurethane sponge and using polydimethylsiloxane as the adhesive and hydrophobic agent, superhydrophobic magnesium hydroxide/aluminum hydroxide @Ni-MOF@polydimethylsiloxane polyurethane sponge is solved, and the problem of hydrophilicity of polyurethane sponge in oil-water separation is achieved, and the efficient oil-water separation and flame retardant performance is improved.
Patent Information
- Application Number
- CN202510028076.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-18
AI Technical Summary
Existing polyurethane sponges are hydrophilic and oil-friendly in oil-water separation, which is difficult to separate, and have insufficient flame retardant properties, which cannot effectively prevent fires caused by oil leakage.
Superhydrophobic magnesium hydroxide/aluminum hydroxide @Ni-MOF@polydimethylsiloxane polyurethane sponge is constructed by loading Ni-MOF and magnesium hydroxide or aluminum hydroxide on a polyurethane sponge and using low surface energy polydimethylsiloxane as a binder and hydrophobic agent.
It achieves high efficiency of oil-water separation, with a separation efficiency of 98.80%-99.89%, and has excellent superhydrophobicity and flame retardant properties to effectively prevent fires caused by oil leakage.
Smart Images

Figure CN119633777A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, and in particular relates to a super-hydrophobic MOF-based polyurethane sponge added with a green inorganic flame retardant for oil-water separation and a preparation method thereof. Background Art
[0002] In recent years, the demand for oil has increased around the world. However, oil leakage during long-distance transportation can cause fires, which can cause irreversible pollution and damage to the local ecological environment. Therefore, relevant measures are urgently needed to deal with this problem. However, low separation efficiency, high cost, low recyclability, and even additional impacts on the ocean have always been the shortcomings of traditional treatment methods. Therefore, the treatment of oil spills is quite challenging.
[0003] Three-dimensional porous materials have attracted much attention due to their multilayer network structure, high porosity, adsorption capacity, long permeation channels and adjustable pore structure. Polyurethane sponges, which have the advantages of high porosity, high elasticity, low density, high adsorption, easy large-scale manufacturing and interconnected pore volume, are widely used as adsorbents in the field of oil-water separation. However, polyurethane sponges are both hydrophilic and oleophilic, which means that oil and water cannot be separated through PU sponges. Therefore, it is necessary to modify the polyurethane sponge, and increasing the roughness has been proven to be a method that can enable polyurethane sponges to have oil-water separation capabilities.
[0004] Metal-organic frameworks (MOFs) have the advantages of diverse structures, large specific surface area, and regular and ordered pore structures, and are also widely used in oil-water separation. Various studies have shown that the roughness can be effectively improved by loading MOFs on porous materials. At the same time, the central metal unit generates metal oxides at high temperatures, which can catalyze carbonization and inhibit smoke release. However, it is not enough to rely solely on the flame retardancy of MOFs. Therefore, it is urgent to design a green and environmentally friendly superhydrophobic flame retardant material. Summary of the invention
[0005] In order to solve the technical problems pointed out in the background technology part, the present invention provides a super hydrophobic polyurethane sponge for oil-water separation and flame retardancy and a preparation method thereof. The polyurethane sponge is used as a substrate, Ni-MOF and magnesium hydroxide or aluminum hydroxide are loaded onto the polyurethane sponge to improve its roughness, and low surface energy polydimethylsiloxane is used as an adhesive and a hydrophobic agent to successfully construct a super hydrophobic magnesium hydroxide / aluminum hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge, which achieves oil-water separation and flame retardancy and has broad application prospects.
[0006] The main steps of the preparation method of polyurethane sponge are as follows:
[0007] (1) 20 mL of DMF, 20 mL of ethanol and 20 mL of deionized water were added to a beaker in sequence and magnetically stirred. 0.88 g of Ni(NO3)2·6H2O, 0.24 g of TPA and 1.2 g of PVP were weighed and added in sequence, and magnetically stirred for 1 h. Next, the mixture was transferred to a 100 mL autoclave, placed in a 150 ° C blower dryer, and reacted for 10 h. After the reaction was completed, the autoclave was taken out, cooled to room temperature, centrifuged in a centrifuge at 10000 r / min, and washed with DMF, deionized water and ethanol in sequence. Finally, the obtained solid was placed in a vacuum drying oven at 80 ° C and dried for 12 h to obtain Ni-MOF.
[0008] (2) Ni-MOF and magnesium hydroxide / aluminum hydroxide were treated with hydrophobicity respectively. Octadecyltrimethoxysilane / dodecyltrimethoxysilane was grafted onto Ni-MOF to construct superhydrophobic powder. First, 50 mL of ethanol was added to a 100 mL glass beaker, and acetic acid was added dropwise to adjust the pH to 4-5; then 0.5-1.5 mL of octadecyltrimethoxysilane / dodecyltrimethoxysilane was measured with a 10 mL measuring cylinder and added to the mixed solution; finally, 0.5-1.5 g of Ni-MOF powder was added, and after magnetic stirring at a speed of 650 r / min for 12 h, centrifugation, ethanol washing, and drying at 60 ° C were obtained to obtain Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane. 50 mL of n-hexane and 0.5-1.5 mL of octadecyltrimethoxysilane / dodecyltrimethoxysilane were added to a 100 mL beaker, and ultrasonicated for 30 min. After the mixture became turbid, 0.5-1.5 g of magnesium hydroxide / aluminum hydroxide was added. After magnetic stirring at a speed of 650 r / min for 12 h, the mixture was centrifuged, washed with ethanol, and dried at 60° C. to obtain magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane.
[0009] (3) The Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane and magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane successfully prepared in step (2) were added to the n-hexane solution together with polydimethylsiloxane and polydimethylhydrogensiloxane (cross-linking curing agent) in an accurate mass ratio. The mixture was evenly mixed with a magnetic stirrer for 30 minutes to ensure that the components were fully dispersed. Subsequently, the pretreated polyurethane sponge was immersed in the mixed solution and magnetic stirring was continued for 3 hours to promote full contact and reaction between the sponge and the components in the solution. Finally, the sponge was placed in a high temperature environment of 180°C for curing for 1 hour, and magnesium hydroxide / aluminum hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge was successfully prepared.
[0010] Among them, the mass ratio of Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane, magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane, polydimethylsiloxane and polydimethylhydrogensiloxane (cross-linking curing agent) is 1:1:2.3:0.23-1:1:4:0.4, the amount of n-hexane is 40mL, polydimethylsiloxane and polydimethylhydrogensiloxane adopt the commercially commonly used Dow Corning 184 product, the two together constitute a curing system, and polydimethylsiloxane and polydimethylhydrogensiloxane are mixed and stirred in a mass ratio of 10:1 for use in the present invention.
[0011] After pretreatment, the original polyurethane sponge was first ultrasonically cleaned in ethanol for 1 hour, and then ultrasonically cleaned again in deionized water for 1 hour to ensure that impurities on the sponge surface were completely removed. After cleaning, the sponge was placed in an environment of 60°C for drying to achieve an appropriate degree of dryness. The final polyurethane sponge had a single volume of 1 cm 3 , that is, a cube shape of 1cm×1cm×1cm.
[0012] The beneficial effects of the present invention are:
[0013] 1. The present invention provides a green and environmentally friendly flame retardant strategy by using a combination of magnesium hydroxide or aluminum hydroxide and Ni-MOF.
[0014] 2. In terms of oil-water separation, the present invention conducts oil-water separation tests on a variety of organic solvents, and the separation efficiencies of chloroform / water, n-hexane / water, octane / water, dichloromethane / water, benzene / water, and toluene / water are as high as 98.80%, 99.82%, 99.89%, 99.47%, 99.21%, and 99.83%, respectively, showing excellent oil-water separation capabilities and broad application prospects in the field of industrial oil-water separation. The experimental results show that the modified sponge has an excellent purification effect on emulsions of chloroform in water, n-hexane in water, and toluene in water. After treatment, the transmittance of these emulsions is significantly improved, all reaching more than 90%. This result fully proves the high efficiency and excellent effect of the modified sponge in emulsion purification.
[0015] 3. The magnesium hydroxide / aluminum hydroxide @Ni-MOF@polydimethylsiloxane polyurethane sponge / dodecyltrimethoxysilane of the present invention exhibits excellent superhydrophobicity / superoleophilicity, a water contact angle of up to 154°, and excellent oil-water separation ability. After 10 cycles of oil absorption, the oil-water separation efficiency can still reach 99.2%. In addition, the sponge also has excellent flame retardant properties, effectively preventing the risk of secondary fires caused by oil spills, and providing strong protection for environmental protection and industrial safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a schematic diagram of the process of preparing a super hydrophobic polyurethane sponge.
[0017] Figure 2 : XRD spectra of Ni-MOF and magnesium hydroxide before and after hydrophobic treatment in Example 1.
[0018] Figure 3 IR spectra of Ni-MOF and magnesium hydroxide before and after hydrophobic treatment in Example 1.
[0019] Figure 4 This is a water contact angle diagram of the superhydrophobic polyurethane sponge obtained in Example 1.
[0020] Figure 5 This is a picture of the silver mirror phenomenon of the super-hydrophobic polyurethane sponge obtained in Example 1 in water.
[0021] Figure 6 This is a graph showing the adsorption capacity of the super-hydrophobic polyurethane sponge obtained in Example 1 for different organic solvents or oil substances.
[0022] Figure 7 This is a diagram showing the separation efficiency of the super-hydrophobic polyurethane sponge obtained in Example 1 for different organic solvent / water mixtures.
[0023] Figure 8 This is a comparison chart of the adsorption capacity of the superhydrophobic polyurethane sponge obtained in Example 1 after 10 cycles of adsorption of chloroform and n-hexane.
[0024] Fig. 9 It is a comparison chart of the transmittance before and after separation of the super-hydrophobic polyurethane sponge obtained by Example 1 from chloroform in water, hexane in water and toluene in water emulsions.
[0025] Fig.10 For the original polyurethane sponge ( Fig.10 a) Polyurethane sponge loaded with Ni-MOF only ( Fig.10 b) Polyurethane sponge loaded with only Mg(OH)2 ( Fig.10 c) and the super hydrophobic polyurethane sponge obtained in Example 1 ( Fig.10 d) Diagram of the combustion process. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with embodiments, but is not limited thereto.
[0027] Example 1
[0028] (1) Add 20mL DMF, 20mL ethanol and 20mL deionized water to a beaker in sequence and stir magnetically. Weigh and add 0.88g Ni(NO3)2·6H2O, 0.24g TPA and 1.2g PVP to the beaker in sequence and stir magnetically for 1h. Then, transfer the mixture into a 100mL autoclave and place it in a 150℃ blower dryer to react for 10h. After the reaction is completed, take out the autoclave, cool it to room temperature, centrifuge it in a centrifuge at 10000r / min, and wash it with DMF, deionized water and ethanol in sequence. Finally, place the obtained solid in a vacuum drying oven at 80℃ and dry it for 12h to obtain Ni-MOF.
[0029] (2) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 1 mL of octadecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of Ni-MOF powder, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain Ni-MOF@octadecyltrimethoxysilane. 50 mL of n-hexane and 1 mL of octadecyltrimethoxysilane were added to a 100 mL beaker, ultrasonicated for 30 min, and when the mixture became turbid, 1 g of magnesium hydroxide was added, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain magnesium hydroxide@octadecyltrimethoxysilane.
[0030] (3) Add 0.5g of polydimethylsiloxane and 0.05g of polydimethylhydrogensiloxane to 40mL of n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g of Ni-MOF@octadecyltrimethoxysilane and 0.2g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 3h, take out the sponge and squeeze it dry, then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0031] Figure 2The XRD characterization results of Ni-MOF and magnesium hydroxide before and after hydrophobic treatment. In the XRD diagram, the characteristic peaks of Ni-MOF are concentrated in 5°-50°, which is consistent with the characteristic peaks of Ni-MOF reported in the literature, and the peak shape is sharp and there are no other impurity peaks, indicating that Ni-MOF with high purity is prepared. In the spectrum of unmodified Mg(OH)2 nanoparticles, the characteristic peaks of Mg(OH)2 are located at 18.6°, 37.9°, 50.8°, 58.6°, 62.1°, 68.2° and 71.9°, which are consistent with the crystal structure of Mg(OH)2 nanoparticles. After ODTMS silanization modification, the XRD diagrams of Ni-MOF and Mg(OH)2 powders did not change, indicating that the crystal structure of Ni-MOF and Mg(OH)2 powders was not affected by ODTMS.
[0032] Figure 3 The infrared characterization results of Ni-MOF and magnesium hydroxide before and after hydrophobic treatment. In the FTIR graph, in the spectrum of Mg(OH)2 nanoparticles without silanization treatment, the peak at 3700 cm -1 The sharp and narrow peak and 1642cm -1 The peaks at 3700 cm-1 and 3700 cm-2 are respectively attributed to the stretching vibration and bending vibration of the hydroxyl group OH in the Mg(OH)2 nanoparticles. -1 The hydroxyl peak of -1 and 2849cm -1 It is attributed to the stretching vibration of the CH bond in ODTMS, and the -1 The new peak at 1033cm corresponds to the bending vibration of the CH bond in ODTMS. -1 and 743cm -1 The newly appeared peaks at 743 cm-1 are related to Si-O-Si and Si-O-Me in ODTMS. These results confirm that ODTMS is grafted onto Mg(OH)2 nanoparticles. Similarly, the spectra of untreated and silane-treated Ni-MOF are compared, and the peak at 743 cm-1 is -1 The peak corresponds to the Si-O-Me of ODTMS, confirming that ODTMS was grafted onto Ni-MOF.
[0033] (i) Further study the hydrophobic properties, adsorption capacity for oil substances or organic solvents, oil-water separation efficiency and recyclability of the superhydrophobic polyurethane sponge prepared by the present invention to evaluate the oil-water selectivity of the modified sponge.
[0034] (1) Hydrophobicity
[0035] Figure 4The hydrophobic angle of the modified sponge is 154°, and there is a very obvious silver mirror phenomenon underwater ( Figure 5 ), proving that the super-hydrophobic polyurethane sponge prepared by the present invention has excellent super-hydrophobicity.
[0036] (2) Adsorption capacity for oil substances and organic solvents
[0037] The samples were completely immersed in various oils and organic solvents for 5 minutes, and the weights before and after were weighed. Each sample was tested three times and the average value was taken. The oil absorption was calculated using the following formula:
[0038] Q=(m1-m0) / m0
[0039] Where m0 and m1 are the masses of the modified sponge before and after adsorption, respectively, and Q is the adsorption capacity.
[0040] The test results are as follows Figure 6 As shown, the modified sponge exhibits excellent adsorption capacity, and its adsorption capacity can reach 22.6 (n-octane)-78 (chloroform) times of its own weight.
[0041] (3) Oil-water separation ability test
[0042] In order to evaluate the oil-water separation efficiency of the modified sponge, deionized water was mixed with various organic solvents (including chloroform, hexane, octane, dichloromethane, benzene and toluene) in a volume ratio of 1:1. In the experiment, the modified sponge was used to adsorb the organic solvent, and the separation effect was evaluated by measuring the mass change before and after deionized water separation. The calculation formula for the oil-water separation efficiency is as follows:
[0043] η=m b / m a
[0044] Among them, m a Represents the mass of deionized water before separation, m b It represents the mass of deionized water after separation, and η represents the oil-water separation efficiency.
[0045] The test results are as follows Figure 7 As shown, the separation efficiency of the modified sponge for chloroform / water, n-hexane / water, octane / water, dichloromethane / water, benzene / water, and toluene / water is as high as 98.80%, 99.82%, 99.89%, 99.47%, 99.21%, and 99.83%, respectively. These data fully prove that the super-hydrophobic polyurethane sponge prepared by the present invention has excellent performance in oil-water separation, can effectively separate clean deionized water from a variety of oil-water mixtures, and shows its wide application prospects in the field of industrial oil-water separation.
[0046] (4) Recyclability test
[0047] Reusability is also an important indicator for evaluating the oil-water separation performance of sponges. The reusability of PDMS / Ni-MOF / Mg(OH)2@PU in practical applications was evaluated through cyclic absorption, extrusion, and drying tests. Figure 8 As shown in the figure, after 10 cycles of absorption, extrusion, and drying tests, PDMS / Ni-MOF / Mg(OH)2@PU can still maintain superhydrophobicity and superoleophilicity, the water contact angle remains above 150°, and the separation efficiency can reach 99.2%, confirming that PDMS / Ni-MOF / Mg(OH)2@PU has excellent oil absorption and oil-water separation capabilities.
[0048] (II) Compared with ordinary oil-water mixtures, emulsions are more difficult to separate due to their small droplet size, stability, and low interfacial energy. The modified sponge was experimentally investigated for its ability to purify emulsions of chloroform in water, hexane in water, and toluene in water. The specific experimental steps are as follows:
[0049] According to the volume ratio of water to oil (chloroform, hexane, toluene) of 6:1, the two were mixed and stirred at high speed for 6 hours to successfully prepare three water-in-oil emulsions. Subsequently, the modified sponge was placed under external force, immersed in the above three emulsions, and stirred to achieve the emulsion purification process. In order to evaluate the emulsion separation effect, the transmittance of each emulsion before and after separation was measured using a UV spectrophotometer.
[0050] The experimental results are as follows Fig. 9 As shown in the figure, after being treated with the modified sponge, the transmittance of each emulsion was significantly improved, reaching more than 90%. This result fully proves that the modified sponge has excellent efficiency and effect in emulsion purification, and shows its application potential in the field of industrial emulsion separation and purification.
[0051] (iv) The original polyurethane sponge itself is highly flammable. Its porous structure can pass more oxygen and provide more combustion sites. Therefore, improving the flame retardancy of polyurethane is of great significance for its application in the field of oil-water separation.
[0052] The combustion experiment was conducted to compare the original sponge, the polyurethane sponge loaded with only Mg(OH)2, the polyurethane sponge loaded with only Ni-MOF, and the sponge loaded with both Mg(OH)2 and Ni-MOF (all with a volume of 1*1*3cm 3 )'s burning time and burning state. Polyurethane sponge is easy to decompose and burn when close to high-temperature heat sources. During the combustion process, droplets will occur and a large amount of toxic and harmful gases will be released. Therefore, flame retardant modification of polyurethane sponge is a necessary measure.
[0053] The flame retardant properties of PDMS / Ni-MOF / Mg(OH)2@PU were evaluated using a lighter ( Fig.10 ). Experiments have confirmed that PU sponge is very flammable. When the fire source is removed 2 seconds after the PU sponge is ignited, the sponge will shrink rapidly and violently, accompanied by molten droplets. When the PU sponge burns for 4 seconds, the entire sponge is ignited, gradually shrinks, melts, and finally turns into ash.
[0054] The combustion characteristics of PDMS / Ni-MOF / Mg(OH)2@PU are significantly different from those of ordinary PU sponge. When PDMS / Ni-MOF / Mg(OH)2@PU comes into contact with a fire source, its overall color gradually turns red, and this change indicates that the material begins to respond to the heat source. After 3 seconds of contact with the flame, PDMS / Ni-MOF / Mg(OH)2@PU begins a slow combustion process. It is worth noting that no obvious material shrinkage is observed during this process. As time goes by, the flame inside PDMS / Ni-MOF / Mg(OH)2@PU gradually extinguishes itself until the 37th second when it is completely burned. Crucially, during the entire combustion process of PDMS / Ni-MOF / Mg(OH)2@PU, no molten dripping or smoke generation occurs. This observation strongly proves that PDMS / Ni-MOF / Mg(OH)2@PU can effectively inhibit the generation of smoke and the formation of molten droplets during the combustion process, thereby demonstrating its significant advantages in flame retardant properties. The characteristics of this material are of great significance for improving the safety and environmental friendliness of the material.
[0055] Example 2
[0056] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0057] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0058] (3) Add 0.2g polydimethylsiloxane and 0.02g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.05g Ni-MOF@octadecyltrimethoxysilane and 0.05g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 3h, take out the sponge and squeeze it dry, then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0059] The hydrophobic angle of the modified polyurethane sponge is 146°, the adsorption capacity for n-hexane and chloroform are 29 g / g and 72 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 25 s.
[0060] Example 3
[0061] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0062] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0063] (3) Add 0.3 g of polydimethylsiloxane and 0.03 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.1 g of Ni-MOF@octadecyltrimethoxysilane and 0.1 g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for another 3 h, take out the sponge and squeeze it dry. Then put it in a 180 ° C oven and dry it for 1 h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0064] The hydrophobic angle of the modified polyurethane sponge is 147°, the adsorption capacity for n-hexane and chloroform are 28 g / g and 74 g / g respectively, the separation efficiency of n-hexane / water mixture is 97%, and the combustion time is 28 s.
[0065] Example 4
[0066] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0067] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0068] (3) Add 0.4g polydimethylsiloxane and 0.04g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.15g Ni-MOF@octadecyltrimethoxysilane and 0.15g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 3h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0069] The hydrophobic angle of the modified polyurethane sponge is 151°, the adsorption capacity for n-hexane and chloroform are 27 g / g and 75 g / g respectively, the separation efficiency of n-hexane / water mixture is 98%, and the combustion time is 32 s.
[0070] Example 5
[0071] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0072] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0073] (3) Add 0.6g of polydimethylsiloxane and 0.06g of polydimethylhydrogensiloxane to 40mL of n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.25g of Ni-MOF@octadecyltrimethoxysilane and 0.25g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge completely enters the solution. After stirring for 3h, take out the sponge and squeeze it dry, then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0074] The hydrophobic angle of the modified polyurethane sponge is 152°, the adsorption capacity for n-hexane and chloroform are 23 g / g and 55 g / g respectively, the separation efficiency of n-hexane / water mixture is 98%, and the combustion time is 36 s.
[0075] Example 6
[0076] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0077] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0078] (3) Add 0.7g polydimethylsiloxane and 0.07g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.3g Ni-MOF@octadecyltrimethoxysilane and 0.3g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 3h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0079] The hydrophobic angle of the modified polyurethane sponge is 151°, the adsorption capacity for n-hexane and chloroform are 19 g / g and 41 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 36 s.
[0080] Example 7
[0081] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0082] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0083] (3) Add 0.5g polydimethylsiloxane and 0.05g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g Ni-MOF@octadecyltrimethoxysilane and 0.2g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 1h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0084] The hydrophobic angle of the modified polyurethane sponge is 148°, the adsorption capacity for n-hexane and chloroform are 25 g / g and 70 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 32 s.
[0085] Example 8
[0086] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0087] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0088] (3) Add 0.5g polydimethylsiloxane and 0.05g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g Ni-MOF@octadecyltrimethoxysilane and 0.2g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 2h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0089] The hydrophobic angle of the modified polyurethane sponge is 151°, the adsorption capacity for n-hexane and chloroform are 23 g / g and 72 g / g respectively, the separation efficiency of n-hexane / water mixture is 97%, and the combustion time is 33 s.
[0090] Example 9
[0091] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0092] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0093] (3) Add 0.5g polydimethylsiloxane and 0.05g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g Ni-MOF@octadecyltrimethoxysilane and 0.2g magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 4h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0094] The hydrophobic angle of the modified polyurethane sponge is 154°, the adsorption capacity for n-hexane and chloroform are 22g / g and 75g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 36s.
[0095] Example 10
[0096] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0097] (2) The hydrophobic modification steps of Ni-MOF and magnesium hydroxide are the same as those in Example 1.
[0098] (3) Add 0.5 g of polydimethylsiloxane and 0.05 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.2 g of Ni-MOF@octadecyltrimethoxysilane and 0.2 g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5 h, take out the sponge and squeeze it dry. Then put it in a 180 ° C oven and dry it for 1 h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0099] The hydrophobic angle of the modified polyurethane sponge is 152°, the adsorption capacity for n-hexane and chloroform are 26 g / g and 75 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 35 s.
[0100] Embodiment 11
[0101] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0102] (2) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 0.5 mL of octadecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of Ni-MOF powder, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain Ni-MOF@octadecyltrimethoxysilane. 50 mL of n-hexane and 0.5 mL of octadecyltrimethoxysilane were added to a 100 mL beaker, ultrasonicated for 30 min, and when the mixture became turbid, 1 g of magnesium hydroxide was added, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain magnesium hydroxide@octadecyltrimethoxysilane.
[0103] (3) Add 0.5 g of polydimethylsiloxane and 0.05 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.2 g of Ni-MOF@octadecyltrimethoxysilane and 0.2 g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5 h, take out the sponge and squeeze it dry. Then put it in a 180 ° C oven and dry it for 1 h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0104] The hydrophobic angle of the modified polyurethane sponge is 150°, the adsorption capacity for n-hexane and chloroform is 27 g / g and 75 g / g respectively, the separation efficiency of n-hexane / water mixture is 95%, and the combustion time is 30 s.
[0105] Example 12
[0106] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0107] (2) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 1.5 mL of octadecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of Ni-MOF powder, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 ° C to obtain Ni-MOF@octadecyltrimethoxysilane. 50 mL of n-hexane and 1.5 mL of octadecyltrimethoxysilane were added to a 100 mL beaker, ultrasonicated for 30 min, and when the mixture became turbid, 1 g of magnesium hydroxide was added. After magnetic stirring at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 ° C, magnesium hydroxide@octadecyltrimethoxysilane was obtained.
[0108] (3) Add 0.5 g of polydimethylsiloxane and 0.05 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.2 g of Ni-MOF@octadecyltrimethoxysilane and 0.2 g of magnesium hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5 h, take out the sponge and squeeze it dry. Then put it in a 180 ° C oven and dry it for 1 h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0109] The hydrophobic angle of the modified polyurethane sponge is 154°, the adsorption capacity for n-hexane and chloroform are 26 g / g and 76 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 33 s.
[0110] Embodiment 13
[0111] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0112] (2) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 1 mL of dodecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of Ni-MOF powder, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain Ni-MOF@dodecyltrimethoxysilane. Measure 50 mL of n-hexane and 1 mL of dodecyltrimethoxysilane and add them to a 100 mL beaker, ultrasonicate for 30 min, and when the mixture becomes turbid, add 1 g of magnesium hydroxide, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain magnesium hydroxide@dodecyltrimethoxysilane.
[0113] (3) Add 0.5g polydimethylsiloxane and 0.05g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g Ni-MOF@dodecyltrimethoxysilane and 0.2g magnesium hydroxide@dodecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0114] The hydrophobic angle of the modified polyurethane sponge is 151°, the adsorption capacity for n-hexane and chloroform are 22g / g and 71g / g respectively, the separation efficiency of n-hexane / water mixture is 95%, and the combustion time is 31s.
[0115] Embodiment 14
[0116] (1) The preparation steps of Ni-MOF are the same as those in Example 1.
[0117] (2) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 1 mL of octadecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of Ni-MOF powder, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain Ni-MOF@octadecyltrimethoxysilane. Measure 50 mL of n-hexane and 1 mL of octadecyltrimethoxysilane and add them to a 100 mL beaker, ultrasonicate for 30 min, and when the mixture becomes turbid, add 1 g of aluminum hydroxide, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 °C to obtain aluminum hydroxide@octadecyltrimethoxysilane.
[0118] (3) Add 0.5g polydimethylsiloxane and 0.05g polydimethylhydrogensiloxane to 40mL n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g Ni-MOF@octadecyltrimethoxysilane and 0.2g aluminum hydroxide@octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5h, take out the sponge and squeeze it dry. Then put it in a 180℃ oven and dry it for 1h to obtain aluminum hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0119] The hydrophobic angle of the modified polyurethane sponge is 153°, the adsorption capacity for n-hexane and chloroform are 21 g / g and 76 g / g respectively, the separation efficiency of n-hexane / water mixture is 97%, and the combustion time is 25 s.
[0120] Comparative Example 1
[0121] (1) The preparation and hydrophobic treatment steps of Ni-MOF are the same as those in Example 1.
[0122] (2) Add 0.5 g of polydimethylsiloxane and 0.05 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.4 g of Ni-MOF@octadecyltrimethoxysilane prepared in step (1) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for another 3 h, take out the sponge and squeeze it dry. Then put it in a 180°C oven and dry it for 1 h to obtain a Ni-MOF@polydimethylsiloxane polyurethane sponge.
[0123] The hydrophobic angle of the modified polyurethane sponge is 153°, the adsorption capacity for n-hexane and chloroform are 23 g / g and 72 g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 27 s.
[0124] Comparative Example 2
[0125] (1) Magnesium hydroxide@octadecyltrimethoxysilane was prepared in the same manner as in Example 1.
[0126] (2) Add 0.5 g of polydimethylsiloxane and 0.05 g of polydimethylhydrogensiloxane to 40 mL of n-hexane solution and stir magnetically for 30 min to ensure good dispersion. Then add 0.4 g of Mg(OH)2@octadecyltrimethoxysilane prepared in step (1) and mix for 30 min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for another 3 h, take out the sponge and squeeze it dry. Then put it in a 180°C oven and dry it for 1 h to obtain magnesium hydroxide@polydimethylsiloxane polyurethane sponge.
[0127] The hydrophobic angle of the modified polyurethane sponge is 152°, the adsorption capacity for n-hexane and chloroform are 20g / g and 72g / g respectively, the separation efficiency of n-hexane / water mixture is 96%, and the combustion time is 18s.
[0128] Comparative Example 3
[0129] (1) First, add 50 mL of ethanol to a 100 mL glass beaker, and add acetic acid dropwise to adjust the pH to 4. Then use a 10 mL measuring cylinder to measure 1 mL of octadecyltrimethoxysilane and add it to the mixture. Finally, add 1 g of nickel hydroxide, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 ° C to obtain nickel hydroxide @ octadecyltrimethoxysilane. 50 mL of n-hexane and 1 mL of octadecyltrimethoxysilane are added to a 100 mL beaker, ultrasonicated for 30 min, and when the mixture becomes turbid, add 1 g of magnesium hydroxide, stir magnetically at 650 r / min for 12 h, centrifuge, wash with ethanol, and dry at 60 ° C to obtain magnesium hydroxide @ octadecyltrimethoxysilane.
[0130] (3) Add 0.5g of polydimethylsiloxane and 0.05g of polydimethylhydrogensiloxane to 40mL of n-hexane solution and stir magnetically for 30min to ensure good dispersion. Then add 0.2g of nickel hydroxide @ octadecyltrimethoxysilane and 0.2g of magnesium hydroxide @ octadecyltrimethoxysilane prepared in step (2) and mix for 30min. Then immerse the polyurethane sponge in the solution and squeeze out the air to ensure that the sponge is completely immersed in the solution. After stirring for 5h, take out the sponge and squeeze it dry, then put it in a 180℃ oven and dry it for 1h to obtain magnesium hydroxide @ nickel hydroxide @ polydimethylsiloxane polyurethane sponge.
[0131] The hydrophobic angle of the modified polyurethane sponge is 154°, the adsorption capacity for n-hexane and chloroform are 21g / g and 73g / g respectively, the separation efficiency of n-hexane / water mixture is 97%, and the combustion time is 27s.
[0132] The above-described embodiments are only preferred examples for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a super-hydrophobic MOF-based polyurethane sponge with added green inorganic flame retardant, characterized in that: The preparation method steps are as follows: (1) N,N-dimethylformamide, ethanol and deionized water were added to a beaker in sequence, and after being stirred evenly, zinc nitrate hexahydrate, terephthalic acid and polyvinyl pyrrolidone were added, and after magnetic stirring for 1 hour, the mixture was transferred to a high-pressure reactor for constant temperature reaction, and then centrifuged and dried to obtain green powder Ni-MOF; (2) adding octadecyltrimethoxysilane / dodecyltrimethoxysilane to an ethanol solution, adding acetic acid dropwise to adjust the pH to 4-5, adding the Ni-MOF obtained in step (1) after magnetic stirring, and then centrifugally drying after magnetic stirring to obtain Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane; adding magnesium hydroxide / aluminum hydroxide and octadecyltrimethoxysilane / dodecyltrimethoxysilane to a n-hexane solution in a mass volume ratio, and centrifugally drying after magnetic stirring to obtain magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane; (3) Add the Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane and magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane obtained in step (2) to a n-hexane solution according to a mass ratio, stir magnetically to mix evenly, then immerse the pretreated polyurethane sponge therein, stir magnetically and cure at high temperature to obtain a magnesium hydroxide / aluminum hydroxide@Ni-MOF@polydimethylsiloxane polyurethane sponge.
2. The method for preparing a super hydrophobic MOF-based polyurethane sponge as claimed in claim 1, wherein: In step (1), the volume ratio of deionized water, N,N-dimethylformamide and ethanol is 1:1:1; the mass ratio of zinc nitrate hexahydrate, terephthalic acid and polyvinyl pyrrolidone is 0.22:0.06:0.
3.
3. The method for preparing a super hydrophobic MOF-based polyurethane sponge as claimed in claim 1, wherein: In step (1), the isothermal reaction is maintained at 150° C. for 10 h, and the drying is continued at 80° C. for 12 h.
4. The method for preparing a super hydrophobic MOF-based polyurethane sponge as claimed in claim 1, wherein: In step (2), the mass volume ratio of Ni-MOF, octadecyltrimethoxysilane / dodecyltrimethoxysilane, and ethanol is 0.5-1.5:0.5-1.5:50; the mass volume ratio of magnesium hydroxide / aluminum hydroxide, octadecyltrimethoxysilane / dodecyltrimethoxysilane, and n-hexane is 0.5-1.5:0.5-1.5:
50.
5. The method for preparing a super hydrophobic MOF-based polyurethane sponge as claimed in claim 1, characterized in that: In step (3), the mass ratio of Ni-MOF@octadecyltrimethoxysilane / dodecyltrimethoxysilane, magnesium hydroxide / aluminum hydroxide@octadecyltrimethoxysilane / dodecyltrimethoxysilane, polydimethylsiloxane and polydimethylhydrogensiloxane is: 1:1:2.3:0.23-1:1:4:0.4, and the amount of n-hexane used is: 40 mL.
6. The method for preparing a super hydrophobic MOF-based polyurethane sponge according to claim 1, wherein: In step (3), the mixing time is 30 minutes, the magnetic stirring time after adding the sponge is 3 hours, and the high temperature curing is maintained at 180°C for 1 hour.
7. The method for preparing a super hydrophobic MOF-based polyurethane sponge according to claim 1, wherein: The original polyurethane sponge pretreated in step (3) was obtained by ultrasonicating in ethanol and deionized water for 1 h and then drying at 60°C. The single volume was 1*1*1cm 3 .
8. A super-hydrophobic MOF-based polyurethane sponge prepared by the method according to any one of claims 1 to 7.
9. An application of a super-hydrophobic MOF-based polyurethane sponge prepared by the method according to any one of claims 1 to 7, characterized in that: The super-hydrophobic MOF-based polyurethane sponge is used as an oil-water separation and flame-retardant material.
Citation Information
Cited By
Green synthetic stone protection material and preparation method thereof
CN120841977A